Presentación: Historia del agua y su gestión - Grández Moreno, Félix (2006)
In the issue that launches a new design and diversifies its sections, allpanchis dedicates the central theme to the problem of water and its management. It is not the first time that the magazine addresses this issue. Doing it again, but this time from the perspective of management, is a way of continuing with the commitment that characterizes our editorial line: seeking alternatives for the future of the Andes.